The design of flats (Rusunawa) in Banda Aceh city - Ega Sara (Universitas Syiah Kuala, 2020)
The design of flats (Rusunawa) in Banda Aceh city aim to solve the problem of the increasing number of shelter needs due to the increasing number of population in Banda Aceh every year. To prevent the limitation of residential land in the future, it needs residential buildings that can accommodate a lot of space. This design applies